French Corporate Governance and Executive Remuneration - Cessey, Julien (2012)
Since the beginning of the last decade, executive remuneration has been subject to comments and critics from scholars, but also, and for other reasons, from politicians and the wider public. The recent crisis has intensified these critics. This paper has two objectives: first it aims at filling a gap in knowledge about corporate governance in France. It investigates the structure of French Firms’ ownership and voting structures, and considers recent evolutions in legislation, as well as the first French corporate governance code, published in 2008 by the AFEP-MEDEF. Second, it looks at potential correlations between different executive remuneration elements and the performance they theoretically reward, over the corresponding time period. France is a civil law country. In terms of ownership structure, it can be characterised by block holding and family control, however to a degree lesser than in other civil law countries such as Italy. Voting rights are separate from stock ownership due to different classes of shares, pyramidal ownership structures, and cross-ownership. The State, if less involved than in the past, plays an important role and can prove very proactive towards companies of which it hold stock, especially on politically sensible themes. The dominant governance structure among listed companies is monist, with or without separation of the offices of President of the Board and Managing Director. Directorships in CAC40 companies are concentrated in the hands of a small number of highly educated individuals, who often hold several directorships at a time, creating inter-companies links. Employees have representation rights, as well as possibilities to take part in their company’s profit-sharing. Thus, France can be considered as evolving in a moderate stakeholder-based perspective. There are numerous, recent legal regulations to corporate governance in France. These laws have often been enacted as a reaction to international scandals. In addition, they seem to have often been inspired by other countries, without considering the particularities of the French context. The AFEP-MEDEF Code of 2008 brings a higher level of expectancy concerning transparency of practices and information disclosure, although it does not bring as much innovation as could have been expected. Since criticism focuses, most of the time, on executive 3 remuneration, the Code emphasises particularly disclosure requirements and encourages firms to define the composition and level of remuneration packages in a reasonable and publicly acceptable way. In a general manner, the AFEP-MEDEF Code seems to be applied carefully by most of the companies declaring it as reference code. However, when it comes to the independency of the board, conditions limiting the award of some elements of compensation or communication about details of remuneration, some progress can still be achieved; this could indicate that executives try to preserve their power in spite of their company’s and shareholders’ interests. Data analysis has been realised over 28 of the CAC40 companies, from 2006 to 2010. The variable component of executives’ cash-based compensation has been put in perspective with yearly capitalisation and earnings per euro of capitalisation. Equity-based compensation was tested for correlation on the medium and long term, ie.over 3 and 5 years. No usable correlation was found. This lack of reliable results can be due to a bad quality of the data gathered, but most likely, it originates in the impossibility to take into account the numerous factors that influence the variation in value of equity awarded. It is very likely that in many cases from 2007, the non-award of remuneration has been decided not due to a bad performance of an executive, but rather to the need of boards of Directors to restore companies’ reputation in terms of executive remuneration. It might be interesting to study executive once the economy has become quieter, when sufficient information is made available. Presently, the context is too complex to draw any reliable conclusion on the existence of a link between executive pay and performance.